2019
DOI: 10.1109/access.2019.2936550
|View full text |Cite
|
Sign up to set email alerts
|

Combining Deep Neural Networks and Classical Time Series Regression Models for Forecasting Patient Flows in Hong Kong

Abstract: Deep Neural Networks (DNNs) has been dominating recent data mining related tasks with better performances. This article proposes a hybrid approach that exploits the unique predictive power of DNN and classical time series regression models, including Generalized Linear Model (GLM), Seasonal AutoRegressive Integrated Moving Average model (SARIMA) and AutoRegressive Integrated Moving Average with eXplanatory variable (ARIMAX) method, in forecasting time series in reality. For each selected time series regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The MAPE values for combinatorial models were also significantly smaller than those from the ARIMA and SES models during weekdays and weekends. Compared to the combined ARIMA and ANN models [ 51 ], our proposed combinatorial model has MAPE ranging from 1.93% to 8.34% for day of the week and achieved lower forecast error for daily presentations in most days. For weekday-wise time series, the model was able to accurately predict day visits, with MAPE ranging from 1.93% to 5.27%, which is significantly lower than most of the other hybrid models, such as the EMD-PSO-BPANN model [ 52 ] and the SVR-FA model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPE values for combinatorial models were also significantly smaller than those from the ARIMA and SES models during weekdays and weekends. Compared to the combined ARIMA and ANN models [ 51 ], our proposed combinatorial model has MAPE ranging from 1.93% to 8.34% for day of the week and achieved lower forecast error for daily presentations in most days. For weekday-wise time series, the model was able to accurately predict day visits, with MAPE ranging from 1.93% to 5.27%, which is significantly lower than most of the other hybrid models, such as the EMD-PSO-BPANN model [ 52 ] and the SVR-FA model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have multiple examinations in the hospital, and some examinations have multiple tasks [19][20][21]. Without proper time control, patients will spend a lot of time waiting.…”
Section: Smart Device Applicationsmentioning
confidence: 99%
“…However, the relationship between dengue cases and meteorological features is highly complex and cannot be easily fitted by the classical time series model. The deep learning method offers more advantages for the health care field as compared with the traditional statistical model [25][26][27][28], and is being actively applied in the prediction the prevalence of infectious disease dynamics [29,30]. Lee et al showed that artificial neural networks (ANNs) offer a potential benefit in forecasting fluctuations in the mosquito population (especially the extreme values).…”
Section: Introductionmentioning
confidence: 99%